Healthcare utilization during acute medically attended episodes of respiratory syncytial virus-related lower respiratory tract infection among infants in the United States. - Jason R Gantenberg; Robertus van Aalst; David R Diakun; Angela M Bengtson; Brendan L Limone; Christopher B Nelson; David A Savitz; Andrew R Zullo (PLoS ONE)
Background Respiratory syncytial virus (RSV) is the leading cause of infant hospitalization in the United States. Understanding healthcare utilization associated with medically attended (MA) RSV lower respiratory tract infection (LRTI) might inform research priorities aimed at reducing RSV-associated pediatric morbidity. We described healthcare utilization during acute MA RSV LRTI episodes within a geographically diverse cohort of infants in the United States. Methods We created retrospective cohorts of infants born in the United States from July 1, 2016 through February 29, 2020 in each of three de-identified insurance claims datasets: Merative MarketScan Commercial Claims and Encounters, Multi-State MarketScan Medicaid, and Optum's de-identified Clinformatics ® Data Mart. We identified infants' first MA RSV LRTI diagnosis during their first RSV season and followed them for 7 subsequent days to record outpatient, emergency department, and inpatient hospital utilization. We calculated the number of outpatient visits, emergency department visits, and inpatient hospital stays occurring during this acute episode and estimated the proportion of episodes involving ≥ 2 visits to a given healthcare setting. Results In the CCAE database, we identified 25,409 acute MA RSV LRTI episodes under the specific RSV definition and 69,068 under the sensitive definition. In the MDCD database, these totals were 67,357 and 170,744, while in the CDM database, they were 12,402 and 31,363, respectively. Across data sources, 34%-69% of infants' first acute MA RSV LRTI episodes involve 2 or more visits to a healthcare setting within 7 days. The percentage of episodes involving at least 2 visits ranged from 34-62% among healthy term infants, 38-65% for Palivizumab-eligible infants, and 38-69% for infants with other comorbidities. Conclusions Within a week of their first MA RSV LRTI diagnosis, infants frequently experience at least 2 visits to one or more healthcare settings, regardless of their comorbidity profile. The percentage of MA RSV LRTI episodes involving at least 2 visits to a healthcare setting may vary by insurance claims database, even between commercial payers.